ADRs & its Reporting for ASU Drugs - Need of an Hour (AYUSHDHARA, 2025)
Due to irrational usage of ASU drugs, Adverse Drug Reactions (ADRs) becoming significant concern for Ayurvedic medicine, and it is essential to understand the causes of ADRs, its consequences and adopt prevention strategies to minimise its adverse effects. In present era, scope of pharmacovigilance increasing day-by-day due to increase in ayurvedic pharmaceutical products in market. In Ayurveda, the principle of drug safety emphasizes on factors like drug interactions (Viruddha Dravya), overdosing (Atimatra Dravya Prayoga), Pathya- Apathya during Oushadha sevana kala and individual patient suitability (Satmya). So, It become essential to understand the causes of ADRs, its consequences and adopt prevention strategies to minimise its adverse effects. Ministry of Ayush also launched Ayush Suraksha portal for reporting of ADRs through online mode. Ayush Suraksha focussed on Ayush medicine for betterment of patient safety. This ADR form filling method will refine clinical practices and minimize the same drug reactions on others.